CONVERGENCE IN INDUSTRY EFFICIENCY AND TECHNOLOGY ADOPTION IN AFRICAN TELECOMMUNICATIONS: AN EMPIRICAL STUDY - Moshi, Goodiel (European Scientific Journal, ESJ, 2013)
This analysis is aimed to explore the patterns of convergence in efficiency of telecommunication industry, as well as in adoption of major telecommunication services particularly fixed lines, mobile and internet usage from 2000 through 2009 in 301 African Countries. More specifically, it investigates whether: first, there is presence of sigma convergence; that is whether countries which were lagging behind in terms of efficiency in telecommunication industry have been catching up with the better performing countries. Secondly, whether countries have experienced beta convergence; meaning, countries which were less efficient at the earlier time have become more efficient at the later time and overtaken countries which were more efficient at the base year. Data Envelopment Analysis is used to determine efficiency scores of telecommunication sector across countries and Wilcoxon signed rank and coefficient of variation are employed to test the presence of beta and sigma convergence respectively. In terms of telecommunications efficiency, the study found that countries experienced sigma convergence although at a slower pace, and no evidence for beta convergence except in earlier period, 2000-2001. Regarding telecommunication services, mobile and internet usage exhibited the higher levels of both sigma and beta convergence while fixed lines followed similar trend as industry efficiency pattern. Following these results, it is suggested for policy makers to reduce the the industry efficiency gap by enact incentives to increasing catch-up in efficiency of teletecommunitions industry among countries.